Antiproliferative Activity of New 6-Bromine Derivatives of 7-Anilino-1-Arylisoquinolinequinones - Ibacache-Rojas, J (Sociedad Chilena de Quimica, 2016)
A variety of 6-bromine-containing 7-anilino-1-arylisoquinolinequinones 2a-g were synthesized to evaluate their half-wave potentials and in vitro antiproliferative activity on gastric and leukemia cancer cell lines. The new compounds displayed significant IC50 values in the range: 1.31 to 11.04 μM. The structure activity relationship analysis of the new series suggest that the antiproliferative activity is dependent, in part, on the push-pull electronic effects of the nitrogen and bromine substituents inserted into the redox fragment of the 1-arylisoquinolinequinone scaffold. Linear regression analysis provided satisfactory relationships between the log IC50 and ClogP values for the AGS gastric cancer cell line.
Keywords: Isoquinolinequinones; half-wave potentials; MTT assay; antiproliferative activity